2010
DOI: 10.1002/hfm.20158
|View full text |Cite
|
Sign up to set email alerts
|

Visual lobe shape characteristics of experienced industrial inspectors and inexperienced subjects

Abstract: This article reports research on visual lobe shape differences between experienced industrial inspectors and inexperienced students and the effects of years of inspection experience on lobe-shape characteristics. Comparison of the visual lobes of students and inspectors showed that lobe roundness of the inspectors was higher than that of the students. Also, marked improvement in lobe roundness and regularity for inspectors was evident in those inspectors who had relatively long experience in inspection work, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Recent research on lobe shape has revealed that lobe training with a difficult target can produce a noticeable improvement in lobe area and roundness, and had a significant effect on visual search performance Chiu 2009, Lee and). Interestingly, lobe roundness for inspectors with experience in microscope-inspection tasks was higher than that for students (Chan and Chiu 2010).…”
Section: Introductionmentioning
confidence: 59%
“…Recent research on lobe shape has revealed that lobe training with a difficult target can produce a noticeable improvement in lobe area and roundness, and had a significant effect on visual search performance Chiu 2009, Lee and). Interestingly, lobe roundness for inspectors with experience in microscope-inspection tasks was higher than that for students (Chan and Chiu 2010).…”
Section: Introductionmentioning
confidence: 59%
“…The probability of the target being detected if it lands in the area of visual lobe P 0 can be affected by both physiological factors as well as attention allocation (Chan & Chiu, ; Chan & Tang, ; Koller, Drury, & Schwaninger, ; McCarley, ). In this experiment, because the target and background elements had very similar shapes, identical colors, and moved smoothly in the same direction and at the same velocity, the asymmetric phenomenon in dynamic visual search does not exist (Araujo, Kowler, & Pavel, ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight engineering undergraduate students (24 males and 4 females) of City University of Hong Kong with ages from 19 to 25 (median = 21) years participated in the experiment with course credit. All of them had binocular near acuity of at least nine (20/22 Snellen notation) on the Bausch and Lomb Orthorator and had previously participated in an experiment measuring visual lobe area and shape characteristics [ 18 , 19 ]. The experiment was approved by the City University of Hong Kong’s Human Subjects Ethics Sub-Committee, and all subjects gave written informed consent before participation.…”
Section: Methodsmentioning
confidence: 99%